THE ROLE OF ASTRONOMY IN DETERMINING THE DIRECTION OF THE QIBLA - Wulan Syaputri (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2025)
The purpose of this study is to determine the role of astronomy in determining the direction of the Qibla. This study is a qualitative study using field research techniques (observation, literature study, and documentation). The data sources are primary and secondary data. The data analysis technique used in this study is Miles and Huberman, namely: data reduction, data presentation, and conclusion drawing. The discussion in this study is as follows. The determination of the direction of the Qibla by Muslims in Indonesia has developed over time in line with the development of existing science. Initially, they determined the direction of the qibla to be west, based on the fact that Saudi Arabia, where the Kaaba is located, is west of Indonesia. This was done approximately, without prior calculation or measurement. Therefore, the direction of the qibla was exactly the same as the direction of the sunset. Thus, the direction of the qibla was identical to the west.